Liquidity management, capital structure and their impact on profitability: a study of selected listed manufacturing firms in colombo stock exchange (cse) in sri lanka - Anushiya, A.; Jathurika, M. (University of Jaffna, 2016)
The paper seeks to shed further light of the impact of liquidity management and capital structure on profitability in listed Manufacturing firms in Colombo Stock Exchange (CSE) in Sri Lanka. Following to the existing literature, Liquidity management and Capital structure are important for a better performance of the firms. Consequently the paper explores the impact of liquidity management and capital structure on profitability in Sri Lankan listed companies over a period of five years from 2011 to 2015. The study is based on secondary data on application of the manufacturing companies selected from CSE listing. The study uses the two proxies of liquidity management such as current ratio and quick ratio further use the two proxies of Capital structure such as debt to equity and debt to assets as the independent variables, whereas Return on Assets (ROA) and Return on Equity (ROE) are used as the dependent variable to analyze the research subject. ROAand ROE are considered as proxy for measuring the profitability. Beyond the quantitative statistical measures, explanatory techniques were used in analyzing impacts. The authors hypothesize that liquidity management and capital structure are significant impact on firm's profitability as well as there are a significant association between liquidity management, capital structure. To examine the association and impact, the authors run a Pearson's correlation and regression analysis. Result of this study reveals that there is no significant impact of liquidity management on firm profitability and also there is no significant impact of capital structure on profitability. The researcher recommends that there is a need for an optimum utilization of the available liquidity in a various aspects of investment in order to increase the firms' profitability and firm should maintain the optimal capital structure and thereby maximize the shareholders wealth.
Keywords: Capital structure; Liquidity; Manufacturing sector; Profitability